The Quarterly Journal of Economics Volume 131 November 2016 Issue 4 - Front Cover (Quarterly Journal of Economics, 2016)
Journal Article The Quarterly Journal of Economics Volume 131 November 2016 Issue 4 - Front Cover Get access The Quarterly Journal of Economics, Volume 131, Issue 4, November 2016, Page i1, https://doi.org/10.1093/qje/qjv058 Published: 26 October 2016